Pengaruh Efektivitas Pengendalian Intern Terhadap Tingkat Keberhasilan Kredit Pada Pt. Suzuki Finance Indonesia (SFI) Cabang Manado - Ferly Olan Rumengan; Frendy A.O. Pelleng; Olivia F. Walangitan (JURNAL ADMINISTRASI BISNIS, 2018)
Loan activity by a finance company is an activity that has high risk, there are many problems or constraints - constraints that result in loss. Factors - factors causing the occurrence of problem loans, including bad loans, installment payments, monitoring and pengelolah internal credit, and so on. Therefore, whether the effectiveness of internal control affects the success rate of credit. This study aims to determine how much influence the effectiveness of internal control of credit success rate at PT. Suzuki Finance Indonesia Branch Manado. Credit by Rivai (2013) "Credit Control is a study conducted by account officer on the feasibility of the company, the client's business feasibility, credit needs, profitability, credit repayment and available guarantees to cover the loan application". Internal Control by Mulyadi (2013) "Internal control system includes organizational structure, methods and measures - coordinated measures to safeguard the organization's wealth, check the accuracy and reliability of accounting data, encourage efficiency and compliance with management policies". The type of research used is descriptive quantitative research using correlation coefficient analysis technique Pearson product moment and simple regression analysis. The population was 46 respondents with the data collecting 44 samples, obtained from the determination of sample size using slovin technique. Data collection was done with questionnaires distributed directly to employees and staff of 44 questionnaires. From hypothesis testing, the real research results show that there is a positive influence and significant effectiveness of internal control of credit success rate at PT. Suzuki Finance Indonesia Branch Manado. With the increased effectiveness of internal control over the credit success rate will have an impact on the increasingly tight credit and operational levels can be maximized.Keywords : Effectiveness Of Internal Control, The Success Rate Credit.